2014
DOI: 10.1104/pp.114.240887
|View full text |Cite
|
Sign up to set email alerts
|

bHLH05 Is an Interaction Partner of MYB51 and a Novel Regulator of Glucosinolate Biosynthesis in Arabidopsis

Abstract: By means of yeast (Saccharomyces cerevisiae) two-hybrid screening, we identified basic helix-loop-helix transcription factor05 (bHLH05) as an interacting partner of MYB51, the key regulator of indolic glucosinolates (GSLs) in Arabidopsis (Arabidopsis thaliana). Furthermore, we show that bHLH04, bHLH05, and bHLH06/MYC2 also interact with other R2R3-MYBs regulating GSL biosynthesis. Analysis of bhlh loss-of-function mutants revealed that the single bhlh mutants retained GSL levels that were similar to those in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 136 publications
(204 reference statements)
5
83
0
Order By: Relevance
“…These results reveal the importance of this SID for SAD2 interaction. Previously, the Asp → Asn mutation in the JAZ interaction domain of MYC2 and MYC3 was found to abolish their binding to most JAZ proteins (Fernández‐Calvo et al ., ; Frerigmann et al ., ; Goossens et al ., ). Here, we show that the Asp → Asn mutation (D261N) in MYB4 significantly abolishes the interaction with SAD2.…”
Section: Discussionmentioning
confidence: 98%
“…These results reveal the importance of this SID for SAD2 interaction. Previously, the Asp → Asn mutation in the JAZ interaction domain of MYC2 and MYC3 was found to abolish their binding to most JAZ proteins (Fernández‐Calvo et al ., ; Frerigmann et al ., ; Goossens et al ., ). Here, we show that the Asp → Asn mutation (D261N) in MYB4 significantly abolishes the interaction with SAD2.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have shown a direct link between jasmonic acid (JA) signaling and glucosinolate biosynthesis [74][75][76]. Expression of AtGTR1 is induced by JA treatment [19], which suggests an involvement in plant response to biotic stress.…”
Section: Box 4 a Possible Link Between Phytohormone And Defense Compmentioning
confidence: 99%
“…Furthermore, similar transcription factor complexes have been shown to regulate cell differentiation and cell fate specification in eukaryotes. For example, the interactions between MYB and bHLH family proteins have been shown to activate or repress different gene modules in glucosinolate biosynthesis in Arabidopsis (Figures 4 and 5A; Schweizer et al, 2013; Frerigmann et al, 2014a), and in skeletal muscle differentiation in animals (Kaspar et al, 2005). In addition, depending on the plant lineage, the interactions between MYB, bHLH and WD40 domain proteins have been shown to activate all or a set of biosynthetic genes in anthocyanin and proanthocyanidin biosynthesis (Figure 3, 5A; Goff et al, 1992; Grotewold et al, 2000; Aharoni et al, 2001; Zimmermann et al, 2004; Quattrocchio et al, 2006), as well as the cell differentiation of single-celled trichomes, non-hair root epidermal cells (atrichoblasts) in the embryonic stem and mucilage secretory cells in the outer seed coat (Figure 5B; Payne et al, 2000; Bernhardt et al, 2003; Esch et al, 2003; Zhang et al, 2003; Gonzalez et al, 2009; Li et al, 2009).…”
Section: Regulatory Components In Plant Secondary Metabolismmentioning
confidence: 99%